Effects Of Study Environment and Peer Collaboration on Learning Outcomes with Group Cohesion as A Mediator - Samaya Riaz (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
The purpose of this research is to examine the impact of study environment and peer collaboration on learning outcomes. Additionally, to examine the impact of peer collaboration on learning outcomes. Furthermore, the research investigates the mediating role of group cohesion between study environment, peer collaboration, and learning outcomes. The research design for this study is quantitative and follows a positivist philosophy. A deductive research approach is used to guide the investigation. The research population consists of students at Thal University Bhakkar, with a total student population of 6,000. The sample size for this study is 300 students. Students were selected using a random sampling technique to ensure that the sample is representative of the broader population. Data were collected through surveys, and the analysis was conducted using SPSS and Smart PLS SEM. The findings of the study reveal that the study environment plays a significant role in learning outcomes. Additionally, the study shows that peer collaboration has a notable effect on learning outcomes, with students who manage to balance work and study demonstrating greater academic performance. Most importantly, the research indicates that group cohesion acts as a significant mediator, influencing how study environment and peer collaboration together affect learning outcomes. This study contributes to the literature by providing insights into the interplay between study environment, peer collaboration, and group cohesion in a regional and cultural context